Determination of the Higgs boson spin with a linear e+e− collider - Dova, María Teresa (2002)
The energy dependence of the production cross section of a light Higgs boson is studied at threshold and compared to the expectations of several spin assumptions. Cross section measurements at three centre-of-mass energies with an integrated luminosity of 20 fb-1 allow the confirmation of the scalar nature of the Higgs Boson.